ANALISIS PERWATAKAN TOKOH DALAM NASKAH DRAMA NARASI HATI ECHA KARYA SARI SETYORINI: TINJAUAN PSIKOANALISIS SIGMUND FREUD - Sri Mulyani; Yusra D; Rahmawati (Jurnal Bastra (Bahasa dan Sastra), 2025)
The aim of this research is to describe the characters contained in the drama script Narasi Hati Echa by Sari Setyorini using Singmund Freud's theory. The form of this research is qualitative research. This research approach is a psychoanalytic approach. The data for this research are characters and characterizations related to id, ego and superego in the drama script Narasi Hati Echa by Sari Setyorini. This research data collection technique uses reading and writing techniques. The data analysis technique in this research uses content analysis techniques. The results of research in the drama script Narasi Hati Echa found 22 data consisting of 13 ids, 4 egos and 5 superegos, based on the results obtained in the drama script Narasi Hati Echa it can be concluded that the id, ego and superego are not balanced, in the data It was found that the ID in the drama script was more dominant than the ego and superego. Because the id element in the characters in the drama script Narasi Hati Echa by Sari Setyorini is more dominant, so they act distantly and come out of the id and kill.